1996
DOI: 10.1021/ja9533611
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Information from 42−108-mer DNAs (Complete for a 50-mer) by Tandem Mass Spectrometry

Abstract: Complete sequence information for an "unknown" 50-mer DNA and extensive sequence verification for another 50-mer and 42-, 51-, 55-, 60-, 72-, 100-, and 108-mer DNAs is obtained by electrospray ionization/Fourier transform mass spectrometry that supplies 10-100× higher accuracy and resolving-power data using nozzle-skimmer (NS), collisionally activated, and infrared multiphoton dissociation (IRMPD). In addition to the previously recognized 3′-and 5′-terminal (w and a) ions, internal ions (i) and MS/MS/MS of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
137
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(139 citation statements)
references
References 59 publications
2
137
0
Order By: Relevance
“…In addition to accurate molecular weight determination, mass spectrometry in combination with different fragmentation schemes provides information about sequence and/or structure of the biomolecules. Seminal work by McLafferty and coworkers demonstrated the ability to obtain partial sequence information for DNA oligonucleotides up to 108 nucleotides in length using tandem mass spectrometry techniques on a FTICR spectrometer [7]. By combining various fragmentation schemes, it was shown that complete sequence coverage could be obtained for a 50-mer DNA [7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to accurate molecular weight determination, mass spectrometry in combination with different fragmentation schemes provides information about sequence and/or structure of the biomolecules. Seminal work by McLafferty and coworkers demonstrated the ability to obtain partial sequence information for DNA oligonucleotides up to 108 nucleotides in length using tandem mass spectrometry techniques on a FTICR spectrometer [7]. By combining various fragmentation schemes, it was shown that complete sequence coverage could be obtained for a 50-mer DNA [7][8][9].…”
mentioning
confidence: 99%
“…Seminal work by McLafferty and coworkers demonstrated the ability to obtain partial sequence information for DNA oligonucleotides up to 108 nucleotides in length using tandem mass spectrometry techniques on a FTICR spectrometer [7]. By combining various fragmentation schemes, it was shown that complete sequence coverage could be obtained for a 50-mer DNA [7][8][9]. Other researchers demonstrated that sequence information and identification of modified bases could be obtained by combining fragmentation schemes with ion trap mass spectrometry [10] and triple quadrupole mass spectrometry [11][12][13].…”
mentioning
confidence: 99%
“…Additional advances included external ion accumulation [11], insertion of an external quadrupole for mass selection prior to ion accumulation and detection [12][13][14], and application of a dc voltage gradient to facilitate ion transfer to the ICR cell [12,15]. Dissociation techniques such as collision-assisted dissociation (CAD) [16], infrared multiphoton dissociation (IRMPD) [17], and electron capture dissociation (ECD) [18] can provide extensive backbone bond cleavage for proteins [19] and DNA oligomers [20] for highly efficient analysis of biomolecules in a "topdown" fashion [21,22].…”
mentioning
confidence: 99%
“…Elucidating these mechanisms is of practical importance, since it will facilitate the rational development of MS-based techniques for sequencing. In addition, the dissociation of biomolecules in the gas phase reflects their intrinsic properties, which are of fundamental interest.For oligodeoxynucleotides (ODNs), sequence information can be obtained from the fragmentation behaviour of either the protonated or deprotonated gaseous ions and the dissociation behaviour of both forms has been extensively investigated [1][2][3][4][5][6][7][8][9][10]. The dissociation of deprotonated ODNs, the focus of the present study, has been shown to proceed first by the loss of a nucleobase, adenine (A), guanine (G), cytosine (C) or thymine (T), in its neutral or deprotonated form, followed by fragmentation of the phosphoester bond at the deoxyribose 3Ј C™O bond at the site of base loss to produce (a-base) and w type ions, according to the nomenclature proposed by McLuckey and coworkers [7].…”
mentioning
confidence: 99%
“…However, in this same study the authors noted different trends at higher charge states: A Ͼ C Ϸ G ӷ T (-4); A Ͼ C Ͼ G ӷ T (-5). McLafferty and coworkers, using infrared multiphoton dissociation (IRMPD) and CID implemented with a Fourier transform ion cyclotron resonance mass spectrometer (FT-ICR/MS), observed the following trend for large multiply deprotonated oligonucleotides (up to 100 mers): A Ͼ C Ϸ G ӷ T [9]. In contrast, McLuckey et al did not observe any preferential loss of the nucleobases in CID-ITMS experiments perform on small, but relatively highly charged, ODN anions (4-, 5-and 8-mers) [8].…”
mentioning
confidence: 99%